Designing connected products : UX for the consumer Internet of th ings - Rowland, Claire; Goodman, Elizabeth, 1976-; Charlier, Martin; Light, Ann (Ann Maxine), 1961-; Lui, Alfred (Sebastopol : O'Reilly, 2015)
Networked thermostats, fitness monitors, and door locks show that th e Internet of Things can (and will) enable new ways for people to inter act with the world around them. But designing connected products for co nsumers brings new challenges beyond conventional software UI and inter action design. This book provides experienced UX designers and technolo gists with a clear and practical roadmap for approaching consumer produ ct strategy and design in this novel market. By drawing on the best of current design practice and academic research, Designing Connected Prod ucts delivers sound advice for working with cross-device interactions a nd the complex ecosystems inherent in IoT technology.
What's different about user experience design for the internet of th ings? -- Things : the technology of connected devices -- Networks : the technology of connectivity -- Case study 1: Proteus Digital Health : t he connected pill -- Product/service definition and strategy -- Underst anding people and context -- Translating research into product definiti ons -- Case study 2: Little Kelham : connected home -- Embedded device design -- Interface and interaction design -- Case study 3: Ford SYNC 3 : connected car -- Cross-device interactions and interusability -- Int eroperability -- Case study 4: LOOP : connected pelvic floor exerciser -- Responsible IoT design -- Supporting key interactions -- Case study 5: BRCK : rugged portable WiFi hotspot -- Designing with data -- Iterat ive design : prototyping and learning -- Designing complex, interconnec ted products and services.
Includes bibliographical references and index.
Keywords: User interfaces (Computer systems); User-centered system design; Ubiquitous computing; Internet of things; Human-computer interaction